Surface segregation of Sn and Sb in the low index planes of Cu - Asante, Joseph Kwaku Ofori (University of the Free State, 2005)
In this study, the segregation parameters for Sn and Sb in Cu were determined for the first time using novel experimental procedures. Sn was first evaporated onto the three low index planes of Cu(111), Cu(110) and Cu(100) and subsequently annealed at 920 oC for 44 days to form three binary alloys of the same Sn concentration. Experimental quantitative work was done on each of the crystals by monitoring the surface segregation of Sn. Auger electron spectroscopy (AES) was used to monitor the changes in concentration build up on the surface by heating the sample linearly with time (positive linear temperature ramp, PLTR) from 450 to 900 K and immediately cooling it linearly with time (negative linear temperature ramp, NLTR) from 900 to 650 K at constant rates. The usage of NLTR, adopted for the first time in segregation measurements, extended the equilibrium segregation region enabling a unique set of segregation parameters to be obtained. The experimental quantified data points were fitted using the modified Darken model. Two supportive models – the Fick integral and the Bragg-Williams equations - were used to extract the starting segregation parameters for the modified Darken model that describes surface segregation completely. The Fick integral was used to fit part of the kinetic section of the profile, yielding the pre-exponential factor and the activation energy. The Bragg-Williams equations were then used to fit the equilibrium profiles yielding the segregation and interaction energies. For the first time, a quantified value for interaction energy between Sn and Cu atoms through segregation measurements was determined (Ω.CuSn = 3.8 kJ/mol). The different Sn segregation behaviours in the three Cu orientations were explained by the different vacancy formation energies (that make up the activation energies) for the different orientations. The profile of Sn in Cu(110) lay at lowest temperature which implies that Sn activation energy was lowest in Cu(110). Sb was evaporated onto the binary CuSn alloys and annealed for a further 44 days resulting in Cu(111)SnSb and Cu(100)SnSb ternary alloys. Sn and Sb segregation measurements were done via AES. The modified Darken model was used to simulate Sn and Sb segregation profiles, yielding all the segregation parameters. Guttman equations were also used to simulate the equilibrium segregation region that was extended by the NLTR runs to yield the segregation and interaction energies. These segregation values obtained from the modified Darken model for ternary systems completely characterize the segregation behaviours of Sn and Sb in Cu. For the ternary systems, it was found that Sn was the first to segregate to the surface due to its higher diffusion coefficient, which comes about mainly from a smaller activation energy (ESn(100) = 175 kJ/mol and ESb(100) = 186 kJ/mol). A repulsive interaction was found between Sn and Sb (Ω.SnSb = - 5.3 kJ/mol) and as a result of the higher segregation energy of Sb, Sn was displaced from the surface by Sb. This sequential segregation was found in Cu(100) (ΔGSb(100) = 84 kJ/mol; ΔGSn(100) = 65 kJ/mol) and in Cu(111) (ΔGSb(111) = 86 kJ/mol; ΔGSn(111) = 68 kJ/mol). It was also found that the profile of Sn in the ternary systems lay at lower temperatures due the higher pre-exponential factor (DoSn(binary) = 9.2 × 10-4 m2/mol and DoSn(ternary) = 3.4 × 10-3 m2/mol) if compared to the binary systems. This study successfully and completely describes the segregation behaviour of Sn and Sb in the low index planes of Cu.
Thesis (Ph.D. (Physics))--University of the Free State, 2005
Keywords: Surface chemistry; Segregation (Metallurgy); Surfaces (Physics)